The Role of Financial Slack as a Mediating Variable between Corporate Governance’s Effect on Company Performance - Perdanaputra, Mahardika; Hersugondo, Hersugondo (Universitas Pendidikan Ganesha, 2024)
Amid the backdrop of the global pandemic, the economic sector has witnessed a profound transformation, with one of its notable consequences being the disruption of businesses, particularly in their struggle to access external resources. In this dynamically altered landscape, the imperative role of corporate governance practices within company management becomes pronounced. These practices are pivotal in orchestrating the efficient allocation and utilization of internal resources, evolving from a mere survival strategy to a competitive advantage, thereby bolstering overall company performance and ensuring sustained viability in the fiercely competitive modern business arena. The type of research used is descriptive research, and the research design employed is longitudinal design. The data that used for this research is 588 data from 98 listed manufacturing companies on the IDX from 2015 – 2020. All data is obtained from company financial reports and also from Bloomberg. Using multiple linear regression analysis and path analysis with SPSS version 25, the results showed that the company's internal resources (slack) could not mediate the relationship between corporate governance and company performance. This shows that company management has not been able to maximize the use of the company's internal resources (slack) in order to improve company performance. The results of this study can be used as input for company management to be able to maximize or use the company's internal resources (slack) properly in order to help the company improve its performance, because all decisions regarding the use of company resources are in the hands of company management.